ASSET BASED COMMUNITY DRIVEN DEVELOPMENT (ABCD): EFFORTS TO DEVELOP VILLAGE POTENTIAL - Sukardi Abbas; Juniartin Husen; Lintal Muna; Rosita Tabaika; Dina Rahmawati (IAIN Ternate, 2020)
Based on the asset-based service model, this study identifies the potential and strength of the Balbar Village community to support the community in developing their natural resource potential. The findings of this service program reveal that the community in Balbar Village has natural resource potential such as coastal and marine ecosystems, plantation areas and house yards, and rivers that cross rural areas. From these assets, the team together with the community recommends further activities such as the development of coastal ecotourism and a sustainable food house program.Keywords: ABCD, village potential